JURIDICAL REVIEW OF MONEY LENDING AGREEMENTS DECLARED VOID BY LAW - Muhammad Nur Ukasyah (Sean Institute, 2022)
This study aims to determine whether the decision of the West Jakarta District Court Judge who decided on the Loan Agreement between Nine AM Ltd. with PT. Bangun Karya Pratama Lestari is null and void in accordance with the law of agreement or not and to find out the juridical implications of the West Jakarta District Court Decision in Case No. 451/Pdt.G/2012/PN.Jkt.Bar regarding the cancellation of the loan agreement. This study uses a normative legal research type using a statute approach and a case approach. The results of this study are 1) The decision of the West Jakarta District Court is in accordance with the law of the agreement that the agreement is null and void. This is because the Loan Agreement has violated the provisions of Article 1320 of the Civil Code, namely the non-fulfillment of the element of a lawful cause and contrary to Article 31 of the Language Law and Article 1339 of the Civil Code which stipulates that an agreement is not only bound to what is expressly agreed. in the agreement, but also bound by propriety, custom, and law. 2) The juridical implication of the decision is that any agreement that is not made in accordance with the provisions of Article 31 of the Language Law will be declared null and void/the agreement is deemed to have never existed and the parties are returned to their original condition. Likewise, any accompanying agreement (accessoir) will also be declared null and void, even though the agreement is made in the presence of an authorized official